MENINGKATKAN KEMAMPUAN PENGENALAN SAINS SEDERHANA MELALUI METODE BERMAIN PENGUKURAN KELAS B TAMAN KANAK-KANAK - Sri Ayu Laali (Universitas Negeri Gorontalo, 2021)
Learning science for children in an effort to grow thinking skills really requires the participation of educators for parents, teachers and other adults. The research objective was to determine the ability of simple science recognition skill through playing measurement method of class B at TK Negeri Pembina Banggai Regency. This research used Classroom Action Research (CAR). The subject of this research were 15 children in group B. The results obtained that children developed and showed better results, especially the children in group B. Science is an activity of tracing, observing and doing an experiments. It is necessary for young children to participate in the scientific process, because the skills that they will acquire can be carried over to further developments and will be useful throughout their life.